REEXAMINING THE ROLES OF PARENTS AND TEACHERS IN ISLAMIC EDUCATION - Nur Said Mutakhir; Syarifuddin Ondeng; Munawir Kamaluddin (PT Altin Riset Publishing, 2026)
The transformation of social environments and the rapid development of digital technology have significantly influenced children’s character formation and Islamic educational development. These changes require stronger collaboration between parents and teachers because the responsibility for children’s education cannot be effectively fulfilled by either family or school independently. This study aims to analyze the roles of parents and teachers in Islamic education and examine how collaborative practices between both parties contribute to the formation of students’ religious character, moral values, and adaptive competencies. This study employed a qualitative approach with a descriptive interpretive design. Data were obtained through interviews, observations, and relevant documentation concerning parental involvement, teacher roles, communication patterns, and collaborative educational practices. The findings indicate that effective collaboration between parents and teachers is manifested through four interconnected dimensions: value reinforcement at home, continuity of Islamic character education at school, reciprocal communication, and joint monitoring of students’ social and digital behavior. The findings further demonstrate that collaboration becomes increasingly important in responding to changes in children’s social environments, particularly the influence of digital media and virtual interaction. Parents primarily provide foundational religious values and emotional support, while teachers strengthen, systematize, and develop these values through educational processes. Therefore, sustainable collaboration between families and schools represents a strategic mechanism for maintaining the continuity of Islamic education and strengthening students’ moral and spiritual development.